1996
DOI: 10.1161/01.str.27.5.897
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Nondominant Hemisphere and Undamaged Area During Word Repetition in Poststroke Aphasics

Abstract: This study shows the importance in aphasic patients of the mirror regions of the left PIF and PST in the nondominant (right) hemisphere for performing the word repetition task. The results also show the importance for nonfluent aphasic patients of the recruitment of the undamaged PIF for spontaneous speech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(82 citation statements)
references
References 24 publications
3
78
1
Order By: Relevance
“…This hypothesis has even been used as the conceptual basis for several neuroimaging studies of lesion-related language disorders (e.g., Refs. 54,67,273,402,419). The contribution of specific right-sided regions in language recovery from aphasia has gained support from recent results.…”
Section: Language Recovery Poststrokementioning
confidence: 98%
“…This hypothesis has even been used as the conceptual basis for several neuroimaging studies of lesion-related language disorders (e.g., Refs. 54,67,273,402,419). The contribution of specific right-sided regions in language recovery from aphasia has gained support from recent results.…”
Section: Language Recovery Poststrokementioning
confidence: 98%
“…Furthermore, more recent clinical studies have emphasized the role of the right hemisphere in spontaneous recovery of language (Thulborn, Carpenter, & Just, 1999;Mimura et al, 1998;Weekes, Coltheart, & Gordon, 1997;Ohyama et al, 1996;Weiller et al, 1995;Papanicolaou, Moore, Deutsch, Levin, & Eisenberg, 1988). Imaging results have shown shifts of activity to right hemisphere areas homotopic to the classical left hemisphere language areas (Ohyama et al, 1996;Weiller et al, 1995), overall stronger activity in the right than in the left hemisphere (Cao, Vikingstad, George, Johnson, & Welsch, 1999;Papanicolaou et al, 1988), or pronounced increase of right hemisphere activity during recovery (Thulborn et al, 1999). In all these studies, aphasic subjects were still in the process of spontaneous recovery (acute state).…”
Section: Role Of Right Hemisphere In Aphasia Recovery and Rehabilitationmentioning
confidence: 99%
“…So far, functional imaging of recovery of language functions in aphasia has largely concentrated on spontaneous recovery (Warburton, Price, Swinburn, & Wise, 1999;Karbe et al, 1998;Buckner, Corbetta, Schatz, Raichle, & Petersen, 1996;Ohyama et al, 1996;Engelein et al, 1995;Weiller et al, 1995;Heiss, Kessler, Karbe, Fink, & Pawlik, 1993;Heiss, Kessler, Thiel, Ghaemi, & Karbe, 1999;Demeurisse & Capon, 1987). The mechanisms of spontaneous recovery are likely to be different from those of training-induced recovery (cf.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, however, other reports have also emphasized the involvement of the right hemisphere in some language functional recovery in a subgroup of post-stroke patients. For example, in the PET study by Ohyama et al (1996), language functional recovery correlated significantly with the activation of the right hemisphere in non-fluent aphasic post-stroke patients. Using functional MRI with language tasks, Abo et al (2004) showed that complete recovery of aphasic symptoms was associated with significant activation of the right hemisphere.…”
Section: Are the Compensatory Areas For Impaired Language Function Unmentioning
confidence: 96%